(untitled) (CIPEEX, 2025)
The objective of this work is to demonstrate that law is always a phenomenon verifiable in social reality; it is a social fact, so the law, conceived as a social fact, transcends the mere collection of legal norms, as an intrinsic manifestation of human interactions within a society. This sociological view of law underlines the importance of social relations and cultural structures in the formation and application of legal norms. By treating law as a social fact, we recognize that it does not arise in isolation, but is influenced and shaped by the historical, economic, political and cultural contexts in which it is inserted. This understanding allows a deeper analysis of the functions and impacts of law in everyday life, revealing how laws reflect and perpetuate the values and power dynamics of a society. Law as a social fact is a perspective that understands law not only as a set of norms and laws, but as a social phenomenon that arises from the interactions and relationships between individuals and groups within a society. According to this view, law is shaped by customs, values, and social practices, and is an expression of the needs and conflicts that exist within a community. It serves to organize and regulate these interactions, seeking to maintain order and promote social justice. Law, therefore, is not static, but dynamic and subject to change as society evolves. Legal norms reflect the historical, cultural and economic conditions of a specific society at a given time. When considering law as a social fact, the importance of the social and cultural context in the formation and application of legal norms is highlighted. From the perspective of legal sociology, law is not the result of a particular vision of an individual, but a phenomenon, or a fact that occurs in the social environment. Law is not the abstract norm, model of language, but a fact that is produced and verified from the social environment.